Tourism direct GDP: Configuration of antecedents and tourism future performance in high-income countries - Agostinho, M.; Dias, Á.; Pereira, L. (Journal of Tourism Futures)
Purpose: This study aims to provide a new perspective on the factors determining a country's tourism performance, understand the interrelationships among these factors, and explore their implications for the future of tourism in high-income countries. Methodology: The study employs a Fuzzy-Set Qualitative Comparative Analysis (fsQCA) using five variables from the World Economic Forum's Travel and Tourism Development Index (TTDI). The focus is on identifying seven configurations of antecedents of Travel and Tourism Industry Gross Domestic Product (T&T Industry GDP). Findings: The study identifies seven configurations of antecedents influencing T&T Industry GDP, revealing how these factors operate in different scenarios, specifically in countries with high and low T&T GDP. These configurations offer insights into potential future pathways for tourism development. Implications: The study implies that tourism is a complex phenomenon influenced by multiple interacting factors. It provides a framework for understanding how different combinations of factors can lead to high or low tourism performance, offering valuable insights for anticipating and shaping the future of tourism. Value: This study adds value by providing a more nuanced understanding of the tourism industry, challenging the notion of singular effects of variables, and highlighting the importance of analyzing multiple, interacting factors in understanding and predicting tourism performance. It contributes to the field of futures studies by offering a tool for anticipating potential future scenarios and their impact on the tourism industry.